Consumer Engagement and Value Capture in Digital Food Waste Platforms Across Different Cultural Contexts - Mudiyanse, Thilini (My University, 2024)
This research provides several essential contributions to the fields of circular economy, sustainability, and digital platforms. First, it enhances our understanding of value creation in contexts such as food waste platforms, where network externalities and the buildup of stakeholder trust are crucial. By integrating previous theories on platform economics, this work enriches the literature on multi-sided platforms and offers practical advice for platform managers seeking to expand their services both locally and internationally. Secondly, the study reveals that culture can serve as both an advantage and a constraint for user adoption, highlighting the imperative need to develop specific strategies that account for local peculiarities in different countries. Therefore, it can be concluded that when expanding into foreign markets, strategies addressing cultural differences present opportunities for the sustainable growth of digital platforms and for maintaining reliable stakeholder interactions in the future. The study also provides valuable insights for other platform operators on how to increase user interactions based on behaviours analysed herein, as well as on the importance of heterogeneous local marketing strategies and approaches to enhance trust. The findings suggest that any platform targeting global markets must differentiate economic benefits, such as the lowest prices of offered foods, from culturally appropriate sustainability communications. Furthermore, many organizations have established or considered forming strategic partnerships with local entities as effective means of overcoming entry barriers and sustaining growth in new markets. For policymakers, this research underscores the importance of implementing circular economy measures to ensure that digital platforms contribute positively to achieving broader public goals, such as combating hunger and reducing waste. In conclusion, this study offers rich insights into strategies that create value within the circular economy context of food waste platforms, explores how digital solutions can facilitate two-sided markets, and discusses the management of the internationalization of digital platforms.
Keywords: consumers; digitalisation; value creation; platform economy; consumer behaviour; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business